DOI: 10.25148/etd.fi14061573
|View full text |Cite
|
Sign up to set email alerts
|

The analytical determination of the uniqueness and persistence of the volatile components of human scent using optimized collection methods

Abstract: Curran, Allison Marsh, "The analytical determination of the uniqueness and persistence of the volatile components of human scent using optimized collection methods" (2005

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 64 publications
(109 reference statements)
0
22
0
Order By: Relevance
“…Solid phase micro extraction gas chromatography mass spectrometry (SPME-GC/MS) was used to analyze the headspace (the gaseous constituents of a closed space above a liquid or a solid sample) of hand odor samples which were collected on sorbent materials and it was determined that the headspace consisted of various classes of compounds which were classified into seven groups; acids, alcohols, aldehydes, hydrocarbons, esters, ketones and nitrogen containing compounds. This study also showed that there was a sufficient degree of variability between a sixty subject population to allow for discrimination between the subjects (24 (26). Specific terms were "coined" by a research group at Florida International University to describe human scent.…”
Section: Chemical Composition Of Human Scentmentioning
confidence: 69%
See 2 more Smart Citations
“…Solid phase micro extraction gas chromatography mass spectrometry (SPME-GC/MS) was used to analyze the headspace (the gaseous constituents of a closed space above a liquid or a solid sample) of hand odor samples which were collected on sorbent materials and it was determined that the headspace consisted of various classes of compounds which were classified into seven groups; acids, alcohols, aldehydes, hydrocarbons, esters, ketones and nitrogen containing compounds. This study also showed that there was a sufficient degree of variability between a sixty subject population to allow for discrimination between the subjects (24 (26). Specific terms were "coined" by a research group at Florida International University to describe human scent.…”
Section: Chemical Composition Of Human Scentmentioning
confidence: 69%
“…As a result of the many legal challenges to which scent evidence has been subjected, numerous research groups are now conducting studies to determine instrumentally, the chemical composition of human scent, the uniqueness of human scent and optimal collection techniques for human scent evidence (2,24,27). This is being done in an attempt to provide a scientific basis for the assumptions previously made that canines can discriminate persons due to individuals possessing unique odors.…”
Section: In the Daubert V Merrel Dow Pharmaceuticals Inc Case The Umentioning
confidence: 99%
See 1 more Smart Citation
“…Curran determined that multiple sampling of one individual's odor profile over time does not contain as much variation as that seen amongst members of a population using hand odor 84 . Similar results have been obtained with different biological specimens, showing that peak area arrays for the common human compounds extracted among six monthly samples for an individual have greater correlation than when compared between subjects.…”
Section: Evaluation Of Odor Profiles Of Individuals Over Timementioning
confidence: 99%
“…The optimized conditions are summarized in Table 6. Extraction conditions for hand odor were determined previously by Curran 84 . All subsequent studies involving human subject samplings utilized the optimized SPME conditions established here.…”
Section: Effect Of Salting Outmentioning
confidence: 99%